PURCHASE MANAGEMENT:: an important activity in the companies - Donizeti Revoredo, Daniel; Roberto Regattieri, Carlos (Revista Interface Tecnológica, 2020)
This work had objective to analyze how a company’s purchasing management is carried out, in order to highlight its importance in cost optimization and in considerable profit improvements. The developed research was applied in a company of specialized retail of equipment and supplies of computer. So, for the methodology used in this study, it is considered a qualitative, descriptive and exploratory approach, through means such as field research (case study), documentary and bibliographic. From the surveys carried out, the research identified that the activities related to purchases, involve a series of factors such as development and selection of suppliers, analysis of costs, negotiation, logistics, forecast of changes in demand, among others. Finally, it can be concluded that the good conduct of purchasing management is a fundamental activity for the success of the organization, as it directly impacts the financial health of the company.